Bacterial Spot of Tomato and Pepper in Africa: Diversity, Emergence of T5 Race, and Management - Jibrin, Mustafa Ojonuba; Timilsina, Sujan; Minsavage, Gerald V.; Vallad, Garry E.; Roberts, Pamela D.; Goss, Erica M.; Jones, Jeffrey B. (Frontiers in Microbiology, 2022)
Bacterial spot disease of tomato and pepper is caused by several species in the genus Xanthomonas. Bacterial spot disease was first reported from South Africa by Ethel M. Doidge in 1920. In the ensuing century after the initial discovery, the pathogen has gained global attention in plant pathology research, providing insights into host-pathogen interactions, pathogen evolution, effector discovery such as the first discovery of transcription activation like effectors among many others. Four distinct genetic groups, including Xanthomonas euvesicatoria (synonym X. euvesicatoria pv. euvesicatoria), X. perforans (synonym X. euvesicatoria pv. perforans), X. gardneri (synonym X. hortorum pv. gardneri) and X. vesicatoria are known to cause bacterial spot disease. Recently, a new race of a bacterial spot pathogen which is a product of recombination between at least two bacterial spot species was reported in Nigeria. In this review, our focus is on progress made on the African continent, vis-à-vis progress made in the global bacterial spot research community to provide a body of information useful for researchers in understanding the diversity, evolutionary changes and management of the pathogen in Africa.